1972
DOI: 10.1136/bmj.4.5838.462
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus hominis Infection in Patients with Myeloproliferative and Lymphoproliferative Disorders

Abstract: SummaryInfection with Herpesvirus hominis, often associated with oral ulceration, was found to be more frequent in patients with myeloproliferative and lymphoproliferative disorders than in normal populations or patients with other diseases. This increased frequency was not associated with any deficiency of the humoral antibody response, suggesting a possible impairment of cellmediated immunity. The otherwise untreatable oral lesions appeared to respond effectively to local irradiation. IntroductionThe frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

1973
1973
1987
1987

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Aston et al (5) found HSV shedding in 3 of 54 (5.5%) patients with myeloproliferative and lymphoproliferative malignancy, which is similar to the incidence reported in normal populations (20). Within our patient population, the suppression of lymphocyte transformation to HSV antigen identified patients given both radiation and chemotherapy as being the group at highest risk of HSV reactivation during the first 12 mo of treatment.…”
Section: Cellular Itininunittx In Lyniphotna Patients Before Treatmentsupporting
confidence: 63%
See 3 more Smart Citations
“…Aston et al (5) found HSV shedding in 3 of 54 (5.5%) patients with myeloproliferative and lymphoproliferative malignancy, which is similar to the incidence reported in normal populations (20). Within our patient population, the suppression of lymphocyte transformation to HSV antigen identified patients given both radiation and chemotherapy as being the group at highest risk of HSV reactivation during the first 12 mo of treatment.…”
Section: Cellular Itininunittx In Lyniphotna Patients Before Treatmentsupporting
confidence: 63%
“…Although cases of severe HSV infection in patients with lymphoma are well documented (5,7,19), and one patient in this study had fatal HSV encephalitis, this prospective study suggests that most patients with lymphoma either have no HSV reactivation or have uncomplicated infection. Aston et al (5) found HSV shedding in 3 of 54 (5.5%) patients with myeloproliferative and lymphoproliferative malignancy, which is similar to the incidence reported in normal populations (20).…”
Section: Cellular Itininunittx In Lyniphotna Patients Before Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Herpetic infections are common in immunosuppressed patients with malignant diseases (Aston et al, 1972;Casazza et al, 1966;Lam et al, 1981;Meyers et al, 1980;Muller et al, 1972), and may be life threatening. The oral ulceration and stomatitis caused by HSV may be associated with significant morbidity.…”
mentioning
confidence: 99%